Answer:
Option B
Explanation:
Consider the steps below;
![3x - 4y = 25,\\3x + 2y = 1\\\\3x - 4y = 25,\\+ ( - 3x - 2y = - 1 )\\\\- 6y = 24,\\y = - 4\\\\3x - 4y = 25,\\3x - 4 * ( - 4 ) = 25,\\3x + 16 = 25,\\3x = 9,\\x = 3\\\\Solution, x = 3, y = - 4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3x1qtvux2upbudliacjpg5u5p0waksjwew.png)
To solve this system of equations, I applied process of elimination, which I thought was most convenient. Multiplying the bottom equation by - 1, I added both equations to cancel out the x's and solved for the value of y. Substituting this value of y into the top equation, I solved for the value of x;
Solution ⇒ Option B